An Integrated Platform Innovation in the Sustainable Agribusiness Ecosystem (Case Study: Tani Link as a Knowledge-Based Communication Media) - Maura Crescentiana Ninik Sri Rejeki; Adrianus Yoga Pranata; Alexander Beny Pramudyanto (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
The research aims to analyze the Tani Link platform as a communication media innovation that contributes to a sustainable agribusiness ecosystem. Additionally, it explores how science communication, such as communication media innovation, can strengthen sustainable agribusiness practices. The approach employed in this study was a case study by analyzing the concept and implementation of the Tani Link platform of the digital ecosystem in sustainable agribusiness. Primary data collection was conducted through interviews with three informants, such as the Director of Tani Link, the Tani Link Information Technology Manager, and the beneficiaries of the Tanilink TV broadcast. In addition, the collection of secondary data was performed through document studies on the Tani Link integrated platform (application, website, and YouTube channel @TanilinkTV). The results of the study indicate that Tani Link was an integrated and knowledge-based platform for building a sustainable agribusiness ecosystem transparently, comprehensively, and democratically. Additionally, the research provided empirical insights into the integration of communication media, technology, and information systems to support sustainable agribusiness, economically, socially, and environmentally.